"Santo não é orixá" : um estudo do discurso anti-sincretismo em integrantes de religiões de matriz africana - Silva, Luiz Claudio Barroca da (2010)
From the viewpoint of the manifesto produced and signed by the baianan candomblé religious leaders, at the II World Conference of Orixá Tradition and Culture (II COMTOC), in 1983, proposing a separation between Catholicism and candomblé, our study analyzes the repercussions of anti-syncretic proposals of the participants of the candomblés of Recife and neighboring regions. For this proposal, we employ, as a theoretical and methodological reference the concept of “Inter-discourse” or “Discursive Memory”, present in an “Analysis of Discourse”, and which is understood as a discourse resignified which structurally has another pre-existent. For this discussion, we do this, in partially structured interviews with the participants of the candomblés of Recife and neighboring areas, which favor anti-syncretism, attempting to identify in these interviews, the construction of some identifiable processes, from memory and tradition actually present in the debates of religious African origins.